Gender and Institutional Aspects of Climate-Smart Agricultural Practices: Evidence from Kenya - Bernier, Quinn; Meinzen-Dick, Ruth S.; Kristjanson, Patricia M.; Haglund, E.; Kovarik, C.; Bryan, Elizabeth; Ringler, Claudia; Silvestri, Silvia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
This paper analyses gender differences in awareness and adoption of climate-smart agricultural (CSA) practices. It examines what factors are associated with the likelihood of adoption of a wide range of CSA practices for 376 women and 375 men in two different areas of Kenya. This information is aimed at improving the targeting and design of interventions that are trying to achieve greater and more equitable agricultural development in East Africa and elsewhere. Our results suggest there is still much work to be done in increasing awareness of improved agricultural practices that enhance livelihoods and resilience to change, including a changing climate. Simply put, increasing awareness is necessary to increase adoption.